Comparison of POSSUM and SAPS II in Prediction of Postoperative Mortality in Hollow Viscus Perforation - Kansakar, Prasan; Ghimire, Bikal; Banjara, Megha Raj; Mishra, Parashuram (Journal of Nepal Health Research Council, 2022)
Background: There have been very few studies in the literature assessing various scoring systems to predict mortality in patients with hollow viscous perforation. Scoring systems like POSSUM and SAPS II are among the most widely validated risk predictors. Objective of the study was to compare POSSUM and SAPS II in prediction of mortality in patients undergoing surgery for hollow viscus perforation.Methods: Prospective observational study was conducted at Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal, over a period of 18 months. Ethical approval was obtained from the Institutional Review Board of Institute of Medicine. Informed consent was taken from all the patients. Patients aged less than 16 years, discharged on request and patients in whom no perforation found during surgery were excluded from the study.Results: Among 121 patients enrolled in the study, in-hospital mortality was seen in 19 patients (17.0%). Mean POSSUM score in survivors was 39.7 ± 7.3 and in non-survivors was 52.8 ± 5.8 (p < 0.001). Similarly mean SAPS II score was 16.4 ± 9.7 in survivors and 41.8 ± 6.4 in non-survivors ( p < 0.001). Area under ROC curve was higher for SAPS II (0.964) as compared to POSSUM (0.906) suggesting that SAPS was better.Conclusions: Both POSSUM and SAPS II provided good discrimination between survivors and non survivors in patients undergoing surgery for hollow viscus perforation. SAPS II showed better sensitivity and specificity than POSSUM in predicting mortality.Keywords: Hollow viscus; mortality; perforation; POSSUM SAPS II.